2020
DOI: 10.3390/cells9102308
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Metabolism: Phenotype, Signaling and Therapeutic Targets

Abstract: Aberrant metabolism is a major hallmark of cancer. Abnormal cancer metabolism, such as aerobic glycolysis and increased anabolic pathways, has important roles in tumorigenesis, metastasis, drug resistance, and cancer stem cells. Well-known oncogenic signaling pathways, such as phosphoinositide 3-kinase (PI3K)/AKT, Myc, and Hippo pathway, mediate metabolic gene expression and increase metabolic enzyme activities. Vice versa, deregulated metabolic pathways contribute to defects in cellular signal transduction pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
204
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(257 citation statements)
references
References 272 publications
1
204
0
2
Order By: Relevance
“…Actually, PI3K-Akt signaling has been commonly known to regulate insulin-based glucose metabolism and mutations of the pathway genes resulting in aberrant signaling activation, thus leading to higher amount of glucose uptake [ 46 ]. And activation of PI3K-Akt signaling provokes the expression of HIF-1α, which is a transcription factor generally known be involved in the cellular adaption to hypoxia and modulates cellular anaerobic metabolism [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, PI3K-Akt signaling has been commonly known to regulate insulin-based glucose metabolism and mutations of the pathway genes resulting in aberrant signaling activation, thus leading to higher amount of glucose uptake [ 46 ]. And activation of PI3K-Akt signaling provokes the expression of HIF-1α, which is a transcription factor generally known be involved in the cellular adaption to hypoxia and modulates cellular anaerobic metabolism [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current research, we verified that miR-330-3p directly bound to GLS 3'-UTR and negatively regulated GLS expression. Aberrant energy metabolism, such as increased glutamine catabolism, is one of critical hallmarks of cancer (33,34). In addition to abnormal glycolysis, several previous studies revealed that enhanced glutamine metabolism was correlated with tumor metastasis and poor prognosis in patients with cancer (12,35).…”
Section: Discussionmentioning
confidence: 99%
“…According to the original version of the “Warburg hypothesis”, cancer cells switch to glycolysis from oxidative phosphorylation. However, more recent data indicate that many cancer cells, while upregulating glycolysis (as well as glutaminolysis, and many additional metabolic pathways) can also maintain or even increase their aerobic ATP generation via the stimulation of mitochondrial electron transport [ 101 , 102 , 103 , 104 , 105 , 106 ]. To anthropomorphize: maximizing ATP generation is the cancer cell’s primary “metabolic goal”: whatever biochemical mechanism serves this goal—even if it is ”wasteful” or perhaps useful in the short-term but detrimental in the longer-term—will be deemed ‘good enough’ to satisfy the “short-term thinking” of the cancer cell.…”
Section: Upregulation Of Various H 2 S-producinmentioning
confidence: 99%